1990
DOI: 10.1007/bf01003175
|View full text |Cite
|
Sign up to set email alerts
|

The effect of heating by microwave irradiation and by conventional heating on the aldehyde concentration in aqueous glutaraldehyde solutions

Abstract: The effect of short time heating of aqueous solutions of glutaraldehyde (GA) on relative aldehyde concentration was determined using spectrophotometric analysis. Because free monomeric GA absorbs U.V. light at 280 nm, whereas the alpha, beta polymeric forms absorb at 235 nm, the purity of GA solutions can be expressed as the ratio: A 235 nm/A 280 nm (purification index, P.I.). Heating of 4 ml aliquots of 0.85% distilled aqueous GA solution resulted in an increase of the absorption at 280 nm which is correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Samples can be treated at a standard temperature without the use of any special cooling equipment, since US treatment causes no increase in sample temperature. The main effect of MW irradiation (electromagnetic waves) in histochemistry is to raise the temperature (13,21). What physical principle of ultrasound explains its accelerating effect on the immunohistochem-ical procedure?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples can be treated at a standard temperature without the use of any special cooling equipment, since US treatment causes no increase in sample temperature. The main effect of MW irradiation (electromagnetic waves) in histochemistry is to raise the temperature (13,21). What physical principle of ultrasound explains its accelerating effect on the immunohistochem-ical procedure?…”
Section: Discussionmentioning
confidence: 99%
“…Probably the most common method used in histochemistry is the immunohistochemical localization of antigens in tissue sections by either the immunoperoxidase (21) or the immunofluorescence technique (18), applied to embedded, frozen, or free-floating vibratome sections. Microwave (MW) irradiation has been increasingly used to accelerate these routine and time-consuming histological procedures and to improve immunostaining.…”
Section: Introductionmentioning
confidence: 99%
“…During microwave fixation, the fixative molecules are considered to be dispersed widely and deeply within the tissue, since the water and glutaraldehyde molecules are polar molecules that absorb the energy of the microwaves. The homogeneous rise in temperature leads to rapid diffusion of glutaraldehyde in spite of its low concentration (Ruijgrok et al 1990). The tannic acid also rapidly penetrates into the specimens during microwave irradiation, with excellent preservation of proteins and peptides ).…”
Section: Conditions Of Fixationmentioning
confidence: 98%
“…The direct thermal effect of an increase in temperature would be expected to accelerate the diffusion of aldehyde fixative into tissue and also to increase the cross-linking reaction rate with tissue proteins (Boon and Kok, 1987). In addition, Ruijgrok et al (1990) have shown that rapid heating to 40'C accelerates the conversion of the glutaraldehyde polymers typically found in fiitive solutions to a free monomeric form. The monomers have a higher diffusion rate and are more effective tissue penetrants and cross-linking agents.…”
Section: Introductionmentioning
confidence: 99%